Inhibition of coagulation proteases and thrombosis and sub-chronic toxicological study of a sulfated polysaccharidic fraction from the red alga Gelidiella acerosa - Ismael Nilo Lino de Queiroz; José Ariévilo Gurgel Rodrigues; Ana Luíza Gomes Quinderé; Márjory Lima Holanda; Maria Gonçalves Pereira; Norma Maria Barros Benevides (Acta Scientiarum. Biological Sciences, 2014)
Metabolites isolated from Gelidiella species (Rhodophyta) have been few studied. We evaluated a sulfated polysaccharidic fraction from G. acerosa collected from two Brazilian beaches on the northwestern coast of Brazil (Flecheiras-F and Pedra Rachada-PR) on coagulation proteases and thrombosis. Their toxicity in vivo was also assessed. Enzymatic extractions yielded 1.40%, and similar chromatographic profiles (DEAE-cellulose) were obtained, with fractions (Ga-I→V) containing differences among the relative proportions of sulfate (5-42%), and revealing charge density patterns by electrophoresis. Ga-IV-PR had a discrete effect (3.01 IU mg-1) on normal human coagulation compared with heparin (193 IU mg-1) and was tested on coagulation proteases (thrombin and factor Xa) in the presence of antithrombin and in a model of venous thrombosis in rats using thromboplastin as the thrombogenic stimulus. The systems were inhibited; but at higher doses (>1.0 mg kg-1), this fraction reverted the antithrombotic effect. Regarding the toxicological study, consecutive Ga-IV (9 mg kg-1) for 14 days did not cause mortality in mice, but some biochemical and hematological parameters were discretely altered. Histopathological analysis revealed that increased liver and spleen sizes had no toxicological significance. Therefore, G. acerosa does not biochemically change its matrix polysaccharide composition and proved to be safe antithrombotic agent.